Pemberdayaan warga Bencah Lesung melalui pelatihan pengolahan sampah anorganik menjadi Ecobrick: Empowering Bencah Lesung Residents through Training on Processing Inorganic Waste into Ecobricks - Fitriana, Nur; Putri, Atika Asadita Sarni; Nur, Yana Windra; Tampubolon, Omar Farrakhan (Universitas Hamzanwadi, 2024)
Bencah Lesung village faces significant waste management issues, with local drainage obstructed by improperly disposed waste. This activity aimed to address non-organic waste accumulation in RW 06, Bencah Lesung, Tenayan Raya District, Pekanbaru City, which has led to flooding and other environmental problems. The proposed solution is implementing the ecobrick concept, transforming plastic waste into sustainable construction materials. The study involved 20 residents in training and socialization on making and using eco-bricks. Methods included practical training and active community participation. Results showed a significant increase in community knowledge and awareness post-training. Quantitative data indicated improvements in scores from an average of 2.4 to 4.6 for knowledge about non-organic waste, 2.2 to 4.3 for understanding the environmental impact of plastic waste, 1.9 to 4.8 for skills in making eco-bricks, 2.6 to 4.7 for awareness of sustainable waste management, and 2.8 to 4.9 for the intention to continue making eco-bricks. Ecobricks not only reduce plastic waste but also provide economic and environmental benefits, with items like shoe racks and tables successfully created. This activity highlights the importance of community participation and environmental education to address plastic waste and promote environmental responsibility. The conclusion underscores the importance of innovative and collaborative waste management as a solution to urban environmental problems